Hubungan antara malnutrisi, suplementasi gizi dan malaria pada anak 0-5 tahun - Ari N Probandari (Berita Kedokteran Masyarakat (BKM), 2005)
Backgrounds: Studies in 1950s until 1980s led to the controversial conclusion that malnourished children were less susceptible to malaria infection. In addition, animal studies appeared to support the reported malaria suppressive effect of a poor diet, leading to the perception that malnourished children are less susceptible to malaria infection, morbidity and mortality. The goal of the article was to perform a literature review on recent studies about the interaction between nutrition and malaria among children under 5 years of age which are the most vulnerable group for both malnutrition and malaria. Methods: Literature on nutrition and malaria was searched in Medline and PubMed databases using combinations of the following keywords: malaria, nutrition, malnutrition, micronutrient, iron, zinc, vitamin A, and child. In total, 271 articles from Medline and 222 articles from PubMed were found. Among these, 13 relevant articles were included. Also, an article from other source (searched by Yahoo), i.e. recommendation of relevance to the topic, was included. Results and conclusion: From review of the literature, it is known that there has been a debate about iron supplementation in malaria endemic area in the last decade. However, recent studies show a positive impact of iron supplementation on malaria morbidity and mortality. In addition, a consensus recommendation about iron supplementation in malaria endemic areas was made by the International Nutritional Anaemia Consultative Group (INACG) because of the urgent need to control Iron Deficiency Anaemia (IDA) especially in vulnerable groups: pregnant women and children less than 5 years of age. A debate about other micronutrient supplementation such as zinc and vitamin A in malaria cases also exists. Some studies have found a positive impact of such supplementation in malaria settings, but others have revealed no impact. In addition, studies about the association between protein-energy malnutrition (PEM) and malaria have shown conflicting results. However, the most recent studies have concluded that malnourished children are at higher risk of malaria morbidity than are non-malnourished children. Keywords: malaria, nutrition, malnutrition, micronutrient, iron, zinc, vitamin A, and child